Staff Retention in Hotel Industry: An Empirical Study Amongst Generation Z Working in Five Star Hotels of Mumbai (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Started as an action termed as ‘revenge tourism’ post pandemic, the phenomena seems to be far from over  and the tourism activities in India is galloping. This phenomenon is generating good volume of business activities for  hotels- rooms as well as food & beverages. This surge is creating a dearth towards skilled manpower in hotel industry  and hotels are finding it difficult to retain quality manpower specially youngsters (Generation Z or Gen Z) joining the  industry. Objectives: This study intent to identify the vital factors that contributes towards turnover intention of Gen Z  and mitigate these factors to retain staff for a longer duration. Methodology: This is a quantitative research wherein  three factors of staff retention were identified namely organizational citizenship behavior (OCB), employee engagement  and job satisfaction, five constructs for each factors, namely learning and development culture, safety at workplace,  welfare scheme for staff, leadership, autonomy, work-life equilibrium, recognition to employees by management,  reimbursements, fixed duty hours, job assignments as per skills and education, etc. were drawn and a questionnaire was  designed on the principles of five point Likert’s scale. The locale of study was luxury hotels of Mumbai. The hotels were  either government approved five-star deluxe hotel or five-star hotels of Mumbai or hotels awaiting affiliation of five star. Total 153 responses were collected from staff working in four major revenue generating operational department of  hotels. The data was tested with correlation and regression analysis. Results: As per the study 47.06% respondents with  mean value 4.02 agreed that acknowledgement to employee’s efforts generates loyalty towards an organization, it was  followed by training and development culture 45.75% (mean value 3.90) and job security with 41.83% ratings and mean  value 3.91. Correlation analysis showed strong link between constructs of job satisfaction and employee engagement  but weak link for OCB. When data was run in regression analysis R value for organizational citizenship behaviour  against all the demographic profiles was less than 0.05, therefore it establishes no relationship between the factor and  demographic profiles, however it was well accepted for other two factors. Conclusion: The hotels need to take care  towards duty hours, leave policies, and internal work environment- which should be healthy and conducive to T&D if  they want to retain Gen Z employees.
Keywords: Hotel industry; staff retention; Gen Z; hospitality